Особливості та напрями правового регулювання сільського туризму в Україні - Кафарський, О.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследованы особенности и основные направления развития правового регулирования хозяйственной деятельности в отрасли туризма в целом и в отрасли сельского туризма в частности. Институт правового регулирования туристической деятельности определяется автором как межотраслевой институт, который в основном подпадает под действие хозяйственного права, однако приоритет в регулировании именно сельского туризма имеет аграрное право Украины. In this article features and basic directions of development of the legal adjusting of enterprise activity are investigational by the author in industry of tourism on the whole and in industry of rural tourism in particular. The institute of the legal adjusting of tourist activity is determined by the author as a between sphere institute, which mainly falls under the action of enterprise law, however much priority in adjusting exactly of rural tourism has agrarian law of Ukraine.